Ultrafiltration Membrane Performance Fitted In Dead-End Stirred Filtration Cell (DESFC) In Concentrating Shank Gelatin - Aspiyanto Aspiyanto; Agustine Susilowati; Hakiki Melanie; Yati Maryati (Jurnal Kimia Terapan Indonesia, 2021)
Performance of Ultrafiltration (UF) Membrane fitted in dead-end stirred filtration cell (DESFC) as a membrane-based unit operation is an essential factor in concentrating shank gelatin to produce concentrated gelatin as a food additive. This study aimed to determine the optimum performance and to evaluate the feasibility of commercial UF flat-sheet membranes (1,000, 20,000 and 100,000 MWCO) equipped in DESFC. The experiment was conducted at gelatin and water ratio of  1:0, 1:2, 1:4 and 1:6 in a laboratory scale with stirring speed of 400 rpm and trans-membrane pressure (TMP) of 40 psia for 30 minutes and resulted in retentate (concentrate) and permeate of shank gelatin. The results showed that larger pores size of the membrane and high ratio of gelatin and water increased both permeate flux and rejection. Based on permeate flux and dissolved protein, the optimum separation condition was achieved using UF membranes of 100,000 MWCO and a gelatin and water ratio of 1:6. This optimum condition resulted in permeate flux of 0.0215 mL/cm2.min. and dissolved protein Robs of 100%.